Novel compound heterozygous SUCLG1 variants may contribute to mitochondria DNA depletion syndrome‐9. Issue 9 (28th June 2022) - Chen, Yi‐ming; Chen, Wei; Xu, Yue; Lu, Chao‐sheng; Zhu, Mian‐mian; Sun, Rong‐yue; Wang, Yihong; Chen, Yuan; Shi, Jiaming; Wang, Dan
Abstract: Background: Succinate‐CoA ligase/synthetase (SCS) deficiency is responsible for encephalomyopathy with mitochondrial DNA depletion and mild methylmalonic aciduria. Variants in SUCLG1, the nuclear gene encoding the alpha subunit of the SCS enzyme playing a pivotal role in maintaining mtDNA integrity and stability, are associated with mitochondrial DNA depletion syndrome 9 (MTDPS9). Methods: In this study, we reported an infant with clinical features of MTDPS9 from China. Whole exome sequencing (WES) was used to identify the genetic cause. Bioinformatic analysis and mtDNA level detection were performed to assess pathogenicity. Results: The proband manifested with hypotonia, lactic acidosis, mild methylmalonic aciduria, hearing loss and psychomotor retardation. WES identified new compound heterozygous SUCLG1 variants of c.601A>G (p.R201G) in exon 6 and c.871G>C (p.A291P) in exon 8. Computational analysis predicted that these missense variants might alter structure stability and mitochondrial translocation of SUCLG1. qRT‐PCR showed 68% depletion of mtDNA content in proband as compared to controls. Conclusion: Novel compound heterozygous variants c.601A>G (p.R201G) and c.871G>C (p.A291P) in SUCLG1 may cause MTDPS9 in this family. Our finding should be helpful for molecular diagnosis, genetic counseling and clinical management of SCS deficiency disorders. Abstract : Novel compound heterozygous variants c.601A>G ( p.R201G) and c.871G>C (p.A291P) in SUCLG1 may be responsible for mitochondrial DNA depletion syndrome 9. Our finding should be helpful for molecular diagnosis, genetic counseling and clinical management of SCS deficiency disorder.